Study on Adsorption of Nickel and Methylene Blue in Aqueous Solution by Magnetic Carboxylate-Rich Carbon - Van Dat, Doan; Hoai Thuong, Nguyen; Thi Kieu Ngan, Tran; Thi Thanh Nhi, Le; My Uyen, Dao; Thi Huong, Tran; Hong Hanh, Cong; Van Thuan, Le (VNU Journal of Science: Earth and Environmental Sciences, 2021)
In this study, magnetic carboxylate-rich carbon material (Fe 3 O 4 @CRC) was synthesized via a low-temperature carbonization method and applied as an adsorbent for adsorption of Ni(II) ions and methylene blue (MB) in aqueous solution. The synthesized Fe 3 O 4 @CRC was characterized by various techniques (XRD, FTIR, FE-SEM, TEM, EDX, VSM, and BET). The adsorption kinetics, isotherms, thermodynamics, and the effects of key adsorption factors, including the pH value, initial adsorbate concentration, contact time, adsorbent dose and temperature were investigated in detail. The results showed that Fe 3 O 4 @CRC exhibited a high adsorption capacity for MB and Ni(II) with the maximum adsorption capacity of 187.26 mg/g and 106.75 mg/g, respectively. The adsorption of MB and Ni(II) on Fe 3 O 4 @CRC was a spontaneous and endothermic process, and was best described with the first-order kinetic model, Freundlich (for MB) and Langmuir (for Ni(II)) isotherm models. In addition, Fe 3 O 4 @CRC could maintain a high adsorption capacity after many consecutive cycles. Therefore, the Fe 3 O 4 @CRC material can be used as a highly efficient adsorbent for the removal of heavy metals and dyes from wastewater due to the advantages of high adsorption performance, easy separation, and good reusability.